Basic geophysics - Robinson, Enders A.; Clark, Dean, 1944- (Society of Exploration Geophysicists, 2017)
For a thorough comprehension of the field of geophysics, we need to understand its origins. Basic Geophysics by Enders Robinson and Dean Clark takes us on a journey that demonstrates how the achievements of our predecessors have paved the way for our modern science. From the ancient Greeks through the Enlightenment to the greats of the contemporary age, the reasoning behind basic principles is explored and clarified. With that foundation, several advanced topics are examined, including: the 3D wave equation; ray tracing and seismic modeling; reflection, refraction, and diffraction; and WKBJ migration. The successful integration of the historical narrative alongside practical analysis of relevant principles makes this book an excellent resource for both novices and professionals, and all readers will gain insight and appreciation for the seismic theory that underlies modern exploration seismology.
Title from PDF title page (SEG eBooks Website, viewed 2017-11-15).
Keywords: Geophysics.; elektronické knihy; electronic books